MODELS OF NON-STEADY STATE AND IN QUASI-STEADY-STATE MODEL CALCULATING RUNOFF TIME - Armijo C., Javier (2001)
Experimental data of efflux time for tank with exit pipe are comparad with values calculated by unsteady-state model(NoE) and quasi-steady-state model(SE). The time required to drain the tank calculated by boths modal give the same results when the step size is 0.1 seconds in the numerical solutlon of modal NoE. In some instances the calculations with the NoE modal glve a deviation of ±1% respect to the experimental value.